2018
DOI: 10.1080/0284186x.2018.1426877
|View full text |Cite
|
Sign up to set email alerts
|

PET-adapted therapy for advanced Hodgkin lymphoma – systematic review

Abstract: This systematic review of PET-adapted therapy, mainly based on RCTs, suggests that a change to the treatment paradigm is appropriate in advanced HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Finally, as with previous studies, though PET2-positivity was clearly associated with a higher rate of treatment failures and early progressions, overall, patients with HL had excellent long-term outcomes regardless of PET2 status. Similar results were demonstrated previously, with an overall survival at 2 years ranging from 88 to 98% and at 5 years ranging from 85 to 95% [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, as with previous studies, though PET2-positivity was clearly associated with a higher rate of treatment failures and early progressions, overall, patients with HL had excellent long-term outcomes regardless of PET2 status. Similar results were demonstrated previously, with an overall survival at 2 years ranging from 88 to 98% and at 5 years ranging from 85 to 95% [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…One must ask oneself if the design of the study in this setting was proper and/or ethical since the PET-positive patients are usually salvaged with BEACOPPesc and have better outcomes with 4-year PFS rate being around 70%, although it was nor will be tested in randomized controlled trials. 27…”
Section: European Association Of Hematology Meeting 2018mentioning
confidence: 99%
“…These reflected the poor outcome in these patients with 2‐year mPFS rate being 57.5% in experimental arm and 42% in control arm with HR being 0.6. One must ask oneself if the design of the study in this setting was proper and/or ethical since the PET‐positive patients are usually salvaged with BEACOPPesc and have better outcomes with 4‐year PFS rate being around 70%, although it was nor will be tested in randomized controlled trials …”
Section: What Have We Learned From Echelon‐1?mentioning
confidence: 99%
“…In addition to four studies reporting patients' response to PET responseadapted therapy [60,61,68,73,78], two recent SLRs have investigated PET and HL; one on interim PET results and prognosis concluded that negative interim PET results have a large advantage in terms of OS (moderate certainty evidence) [134]. A review of PET-adapted therapy for HL recommended a PET treatment approach as standard of care for advanced HL [135].…”
Section: Discussionmentioning
confidence: 99%